2019
DOI: 10.1021/acsptsci.9b00037
|View full text |Cite
|
Sign up to set email alerts
|

Antibody-Mediated Delivery of VEGFC Ameliorates Experimental Chronic Colitis

Abstract: Crohn’s disease (CD) and ulcerative colitis (UC) are two distinct forms of inflammatory bowel disease (IBD) characterized by an expanded lymphatic network with impaired functionality both in mouse models and in human patients. In this study, we investigated whether targeted delivery of the pro-lymphangiogenic vascular endothelial growth factor C (VEGFC) to the site of inflammation may represent a new, clinically feasible strategy for treating IBD. To achieve targeting of inflamed tissue, we developed a fusion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 39 publications
(84 reference statements)
0
5
0
Order By: Relevance
“…103 GFs are proteins that can stimulate the regeneration and healing of the intestinal mucosa. 104 However direct use of growth factors tends to reduce the efficacy of the drug due to the stimulation of gastrointestinal digestive fluids. Therefore, carriers are necessary to assist in the delivery of growth factors.…”
Section: Types Of Drugs and Bioactive Substances To Be Deliveredmentioning
confidence: 99%
“…103 GFs are proteins that can stimulate the regeneration and healing of the intestinal mucosa. 104 However direct use of growth factors tends to reduce the efficacy of the drug due to the stimulation of gastrointestinal digestive fluids. Therefore, carriers are necessary to assist in the delivery of growth factors.…”
Section: Types Of Drugs and Bioactive Substances To Be Deliveredmentioning
confidence: 99%
“…VEGFC-promoted lymphangiogenesis reduced inflammation. Similarly, blocking VEGFR-3 or the calcitonin lymphangiogenic receptors resulted in disease exacerbation [114][115][116][117][118][119]. On the contrary, it was shown that the pharmacological inhibition of lymphangiogenesis ameliorated disease activity [120,121], while lymphangiogenesis stimulation by VEGF-C overexepression in the same colitis model aggravated intestinal inflammation [122].…”
Section: The Role Of Lymphatic Vessels and Lymphatic Endothelium Alte...mentioning
confidence: 99%
“…In contrast, resolution of chronic inflammation may require restoration of proper lymphatic function, removing inflammatory cells, mediators, and bacterial antigens from inflamed sites. Systemic treatment with VEGF-C significantly reduced the clinical and histological signs of inflammation, expanded the lymphatic vascular network, reduced the density of immune cells, and decreased inflammatory cytokine expression in the inflamed colon [ 60 ].…”
Section: Histopathological Features Of Inflammatory Bowel Disease (Ibd)mentioning
confidence: 99%